Perubahan budaya mengajar di era digital - Harjuansari, Nasya Putri; Zulaikha, Siti; Maulidianah, Alif Rofa (2021)
This article will discuss teaching and learning in the digital age. This research will contribute to how education should place itself in the changing times, including in facing the digital era. Through this research, researchers get some important aspects regarding teaching and education in the digital age, namely education in the digital age has different characteristics from the education of students in the previous period, the generation at this time is those who do most of their life and educational activities using the media digital to make it easier for them. Students at this time are born, grow and develop in direct contact with the digital world, so that the flow of information obtained will be different from students in the previous period. Therefore, teachers as people who play an important role in the learning process must be able to design learning activities using digital media so that students can get more and varied information than before.